主題式報紙新聞數位典藏之研究－以台灣棒球運動為例 - 林信成(Sinn-Cheng Lin) (教育資料與圖書館學, 2005)
Traditionally, most of the digital newspaper archive systems used all of the report contents to create a complete database. One of the advantages is the collection can cover a broad range of subjects; however the database could he too huge to be made value-add deeply. Therefore, this paper proposes a thematic approach for constructing a digital newspaper archive, and uses the historical reports of Taiwan baseball, which is provided by United Daily News, as case study. First, we work on the system analysis and establishment, then we study on the semantic description and the metadata conversion, such that the resulting digital archive system can he more useful.